Effect of ethyl pyruvate on the artificial insemination liquid of boar spermatozoa - Gamage, Malavi Arachchi Gamage Nayodya Dananjanee Malavi Arachchi; Dissanayake, Wijesooriya Mudhiyanselage Nadeema; Yi, Young-Joo (Journal of Biomedical Translational Research, 2025)
The success of artificial insemination (AI) in the swine industry relies on conserving the quality of boar sperm during liquid storage, as boar spermatozoa are prone to oxidative stress due to the high polyunsaturated fatty acid content and lack of antioxidant defenses. Sperm motility, viability, acrosome integrity, and DNA stability are all affected by the increases in reactive oxygen species (ROS) during storage, which lowers fertility. Ethyl pyruvate (EP), a stable derivative of pyruvate, has good antioxidant properties and has been shown to protect sperm quality in vivo. Its effects on boar sperm during in vitro preservation have not yet been investigated. This study investigated the effect of different concentrations of EP (0.1–1 mM) in Beltsville thawing solution at 17°C on the sperm quality parameters of boar spermatozoa over five days. Changes in sperm motility, viability, acrosome integrity, chromatin stability, and ROS were observed. The results showed that boar spermatozoa stored with 0.25–0.75 mM EP showed a significant increase in sperm motility, viability, acrosome integrity, and chromatin stability compared with the control (without EP) and 1 mM EP for 5 days. Compared to the control and 1 mM EP, ROS levels statistically decreased in sperm stored in 0.25–0.75 mM EP on both storage days 3 and 5. Our findings demonstrated that 0.25–0.75 mM of EP could enhance the boar sperm quality and mitigate the oxidative stress during liquid storage, thus revealing a strategy to improve fertility rates during AI in pig production.